Dynamics of Employee Reactance to Company and Union Dual Allegiance Revisited and Expanded - Thacker, James; Rosen, Hjalmar (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This study examines the relationship between company commitmentand union commitment using the traditional dual allegiance approaches as well as a different methodology which utilizes multiple discriminant function analysis.